The Paradigm of Cyberporn On Legal Culture and Religion Perspective - Prima Angkupi (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2017)
Indonesia as the largest Muslim country should ideally have a society with good legal culture. Criminal offense or a violation related to cyberporn, does not need to happen. Cyberporn crime is not only a legal issue, but it is more complex. The weakness of the legislation, as well as the technological advances that are supported by the low legal awareness of society, it will difficult to tackle the cyberporn crime. The role of religion is needed as ethical teachings. Indonesia, which recognizes the principle of the Deity as its first principle, mean idealizing the condition of religious society. Awareness of the law will also be easily formed in communities that implement the teachings of their religion well, including public awareness for not accessing the cyberporn. : Indonesia sebagai Negara umat muslim terbesar idealnya memiliki masyarakat dengan budaya hukum yang baik. Tindak pidana atau bentuk pelanggaran yang berkaitan dengan cyberporn tidak perlu terjadi. Kejahatan cyberporn tidak hanya merupakan permasalahan hukum, tetapi lebih kompleks. Kelemahan peraturan perundang-undangan serta kemajuan teknologi yang didukung dengan kesadaran hukum masyarakat yang sangat rendah mengakibatkan akan sulit menanggulangi kejahatan cyberporn. Peran agama dibutuhkan sebagai sebuah ajaran etika. Indonesia yang mengakui sila Ketuhanan sebagai sila pertamanya, berarti mengidealkan kondisi masyarakat Indonesia yang religius. Kesadaran terhadap hukum pun juga akan mudah dibentuk dalam masyarakat yang mengamalkan ajaran agamanya dengan baik, termasuk kesadaran masyarakat untuk tidak mengakses cyberporn. DOI: 10.15408/jch.v5i1.3509